Implementing English as a Medium of Instruction: Teachers’ Lived Experiences in Public Schools of Nepal - Dhami, Nirmala (Far Western Review, 2025)
This paper explores the lived experiences and views of basic level teachers of public school regarding the implementation of English as a medium of instruction (EMI). This study primarily focuses on the experiences of teachers of Kanchanpur district who teach health and physical education subject using EMI. This paper further explores how teachers apply the EMI, their level of training considering the difficulties they have when instructing content subject in English. The study adopts a qualitative phenomenological approach to record the practical experiences of teachers with the responsibility of implementing EMI. The data was collected through semi structured interviews with four purposively selected teachers, giving thorough insights. The findings demonstrate that while EMI is viewed as an initiative that attempts to give students global skills, teachers deal with difficulties like insufficient supervision and training, a lack of appropriate teaching resources, and students’ divergent levels of English proficiency. These difficulties make it challenging to teach and learn effectively. The study also emphasizes the significance of enhanced teacher preparation, more access to resources, and a method that considers students’ previous linguistic backgrounds. By addressing these issues, EMI implementation might be improved and students could benefit academically and linguistically from the policy.